Building the Evidence Base on Community Food Production Initiatives in Pacific Island Countries - Iese, V.; Wairiu, M.; Fesaitu, J.; Teva, C.; Navunicagi, O.; Unwin, N.; Haynes, E.; Guell, C.; Francis, Judith Ann (Technical Centre for Agricultural and Rural Cooperation, 2020)
Poor dietary diversity, low consumption of fruits and vegetables, and an increasing reliance on relatively expensive, processed and imported foods high in fat, salt and sugar, are linked to the triple burden of malnutrition. Under-nutrition, overweight and obesity, and micronutrient deficiencies are challenging food and nutrition systems in PICs. Between 40 and 80% of adults are overweight and obese and approximately 15-25% suffer from type 2 diabetes in the region (IDF, 2017 and NCD Risk Factor Collaboration, 2016). These prevalence rates are among the highest recorded globally. Related to this, adults in PICs have a high probability of premature mortality from non-communicable diseases (NCDs). Depending on the PIC, between one in six to one in four women, and one in four to over one in three men, will die from an NCD before their 70th birthday (WHO, 2018). In the seven InnovAg4Pacific project countries, death rates attributable to poor nutrition are around three to seven times higher than in New Zealand. A fifth to a third of all deaths in these countries are attributable to poor nutrition.